Forearc Variability and the Geochemical Diversity of Suprasubduction Zone Ophiolites: Insights From the Leka Ophiolite Complex, Norway - Naomi A. Becker; Wendy R. Nelson; Joseph F. Browning‐Hanson; Freya R. George; James L. Crowley; Daniel R. Viete (Geochemistry, Geophysics, Geosystems)
Abstract New whole‐rock major and trace element geochemistry from the Leka Ophiolite Complex in Norway is presented and compared to the geochemical evolution and proposed tectonomagmatic processes recorded in the Izu‐Bonin‐Mariana system. These data demonstrate that the Leka Ophiolite Complex formed as forearc lithosphere during subduction initiation. A new high‐precision zircon U‐Pb date on forearc basalt constrains the timing of subduction initiation in the “Leka sector” of the Iapetus Ocean to 491.36 ± 0.17 Ma. The tectonomagmatic record of the Leka Ophiolite Complex captures only the earliest stages of subduction initiation and is thereby distinct from some other Appalachian–Caledonian ophiolites of similar age. The diversity of Appalachian–Caledonian ophiolite records may represent differing preservation and exposure of a variable forearc lithosphere.